Developing a Framework of Self-Leadership for Undergraduate Students in Thailand - Zhang, Chongyan (Journal of Modern Learning Development, 2023)
Self-leadership is a topic applied for higher education today, since self-leadership could bring positive growth, develop, and change for students in higher education; Thailand needs to develop social changes successfully, thus the idealistic future leaders need to possess calm, wise and intellectual mindfulness to complex social issues; furthermore, Thailand can provide sufficient resources and platforms to develop self-leadership for students in higher education; thus, the researcher aimed to propose the framework and contribute the development of self-leadership in Thailand; the research was quantitative analysis by the five objectives: 1) to find what levels of self-leadership for undergraduate students in Thailand; 2) to find what levels of activities can assist to self-leadership for undergraduate students in Thailand; 3) to determine whether is significant difference between students’ demographics and self-leadership for undergraduate students in Thailand; 4) to determine whether is relationship between leadership activities and self-leadership for undergraduate students in Thailand; 5) to propose suitable framework of self-leadership for undergraduate students in Thailand. the research conducted random sampling and online questionnaire as the tool of data collection; there were 400 valid data as the analytical data; respondents are undergraduate students from three representative universities in Bangkok, Thailand; the research including the following findings: 1) dimensions of self-leadership suitable for students in higher education in Thailand: outlook, self, action, and reflection; 2) five kinds of activities assist to self-leadership suitable for students in higher education in Thailand: keep energy, good communication, self-regulation, undertake responsibility, and smart decision-making; 3) there were not significant difference between demographics of students and self-leadership for undergraduate students in Thailand (p>.05) ; 4) there were significant relationship between activities and self-leadership for undergraduate students in Thailand (p<.05); 5) the five scholars offered approved results to the validation on the framework (≥0.60), thus, the framework may assist to develop self-leadership for undergraduate students; furthermore, the framework suggested stakeholders can consider organize educational platforms like lectures, seminars, learning programs to students in higher education in Thailand, they can conduct the five activities to assist to enhance self-leadership for students in Thai higher education; in conclusion, by the empirical research, the framework could assist to develop self-leadership for undergraduate students in Thailand, practitioners might adjust the context of the framework in their reality.